Human resource devolution, decoupling and incoherence: how line managers manage gender equality reforms. Issue 10 (2nd October 2020) - Williamson, Sue; Colley, Linda; Foley, Meraiah
ABSTRACT: Public sector human resource management (HRM) has been devolved from central personnel agencies to line agency HRM professionals and further to line managers. While devolution has admirable goals, it has created difficulties as managers have not been sufficiently trained in HRM. We examine these difficulties in Australian public services, through the lens of recent gender equality reforms. We identify that the approach to HRM devolution has contributed to a decoupling of policy and practice and a resulting incoherence, as new policies are introduced by HRM professionals but not effectively communicated to line managers, not effectively implemented, and not monitored.